The role of the Aegean Thrace and Central Northern Greece as natural corridors for early hominin dispersals: current evidence and prospects - Litsios , Panagiotis (Journal of Greek Archaeology, 2024)
The Balkan peninsula is often considered as one of the possible crossroads between Africa and Eurasia for early hominin dispersals. While the rest of the Balkans e.g., Bulgaria has provided secure chronostratigraphic data for the Lower Palaeolithic (LP), e.g., Kozarnika, and later phases of the Pleistocene e.g., Temnata and Bacho Kiro, evidence from Greece was until very recently based on a few isolated lithic findings, and the Petralona cranium which is most commonly dated between 0.3-0.2 Mya. The recent excavations and the emerging new data from the Peloponnese, Marathousa I and II, and the Aegean, Rodafnidia, have provided robust and secure chronostratigraphic data for Middle Pleistocene hominins, shaping a new dynamic picture for the Aegean and the Greek mainland from at least 0.5-0.2 Mya. The LP of Stelida, and Plakias, on the other hand is subjected to an ongoing debate as it has not been adequately addressed by archaeological or absolute dating evidence, and more importantly from securely stratified and contextualized data to support the presence of Middle Pleistocene hominins.